Executive Committee Minutes 2019-05-09 - Academic Senate:::::::::
Agenda – Approved. Minutes of 4/25/19 – Approved. Chair Report. President Report. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. Associated Students Report. From S&F: Request to waive by-laws for URTP semester appointment – Approved. From EPC: Theater Arts BA - Minimal revision to Acting Concentration – Approved for the Senate consent calendar. From EPC: Theater Arts BA - Revision to Dance concentration. From EPC: Revision to GEP – all concentrations. More Provost report. Memo from S&F regarding appeals of Senate decisions – two motions made and approved. Senate Agenda approved.